2020
DOI: 10.1038/s41419-020-02935-7
|View full text |Cite
|
Sign up to set email alerts
|

UBAC2 promotes bladder cancer proliferation through BCRC-3/miRNA-182-5p/p27 axis

Abstract: Emerging evidences have demonstrated that ubiquitin-associated domain-containing protein 2 (UBAC2) is closely related to the occurrence and development of malignant tumors. However, the functions and underlying molecular mechanisms of UBAC2 in bladder cancer (BC) development have not been defined. In this study, we found that both UBAC2 mRNA and protein levels were upregulated in BC tissues and cell lines, and knockdown of UBAC2 inhibited BC cells proliferation both in vitro and in vivo. Meanwhile, Kaplan–Meie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 73 publications
2
6
0
Order By: Relevance
“…Similar to our results, previous studies have confirmed that POIR acts as a sponge of miR-182-5p (Wang et al, 2016). MiR-182-5p is reported to function as a putative oncogenic or tumor-suppressive factor and plays a role in various cancers (Gu et al, 2020;Li et al, 2020b;Yan et al, 2020). In this study, we found that miR-182-5p overexpression resulted in the sensitization of HCC cells to sorafenib, whereas miR-182 inhibition led to elevated sorafenib resistance of HCC cells.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our results, previous studies have confirmed that POIR acts as a sponge of miR-182-5p (Wang et al, 2016). MiR-182-5p is reported to function as a putative oncogenic or tumor-suppressive factor and plays a role in various cancers (Gu et al, 2020;Li et al, 2020b;Yan et al, 2020). In this study, we found that miR-182-5p overexpression resulted in the sensitization of HCC cells to sorafenib, whereas miR-182 inhibition led to elevated sorafenib resistance of HCC cells.…”
Section: Discussionsupporting
confidence: 92%
“…MiRNA is an important post-transcriptional regulator, resulting in a decrease in mRNA expression through direct base pairing with mRNA 3′-UTR target sites [ 30 ]. MiR-182-5p has been proven to regulate the key process in multiple cancers, such as breast cancer, bladder cancer, and colon cancer [ [31] , [32] , [33] , [34] ], but our study is the first to demonstrate its acting as a functional target in the ceRNA network in adipocytes and cachexia.…”
Section: Discussionmentioning
confidence: 78%
“…RNF5, a member of E3 ubiquitin protein ligase, exerts the neuroprotection effect as a downstream molecular of the DJ-1/Akt signaling pathway (Zhang et al, 2012). UBAC2, which serves as a regulator of ER-associated protein degradation, plays a critical role in promoting the occurrence and development of malignant tumors (Gu et al, 2020). It has been reported that the mutation of DNAJC protein family may contribute to Parkinson's disease pathogenesis, suggesting that they may be considered as effective therapeutic targets in neurodegenerative diseases (Roosen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%